Temperature-Corrected Oxygen Detection Based on Multi-Mode Diode Laser Correlation Spectroscopy - Xiutao Lou; Gabriel Somesfalean; Zhiguo Zhang; Shaohua Wu (Journal of Spectroscopy)
Temperature-corrected oxygen measurements were performed by using multi-mode diode laser correlation spectroscopy at temperatures ranging between 300 and 473 K. The experiments simulate in situ monitoring of oxygen in coal-combustion exhaust gases at the tail of the flue. A linear relationship with a correlation coefficient of −0.999 was found between the evaluated concentration and the gas temperature. Temperature effects were either auto-corrected by keeping the reference gas at the same conditions as the sample gas, or rectified by using a predetermined effective temperature-correction coefficient calibrated for a range of absorption wavelengths. Relative standard deviations of the temperature-corrected oxygen concentrations obtained by different schemes and at various temperatures were estimated, yielding a measurement precision of 0.6%.